O trudnej sztuce tworzenia siebie w kulturze edukacji. W stronę myśli Harolda Blooma - Nawrocki, Radosław (Studia Edukacyjne, 2021)
The purpose of this text is to reflect on the process of building individual identity in the culture of education. The adopted perspective is based primarily on the concepts of culture and the place of the subject in it, derived from the thought of Richard Rorty and Harold Bloom. This perspective affords a look at the process of building an individual in a mature way, devoid of naivety but also revealing the hardships and aporias accompanying this process. Education can be the primary way through which man tries to get along with the world. The condition for the fortunate effect of these struggles is building a culture that is democratic, or in Rorty’s words poetic.